SYSTEMATIC LITERATURE REVIEW: GAMIFIKASI TERHADAP PEMAHAMAN KONSEP MATEMATIS DAN SELF-EFFICACY - Azzahra, Fricinta Felina; Nindiasari, Hepsi; Novaliyosi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of gamification on students’ mathematical concept understanding and self-efficacy through a Systematic Literature Review (SLR) approach. This research is motivated by the low level of students’ mathematical concept understanding indicated at approximately 39% and the critical role of self-efficacy in supporting learning achievement. The method used is an SLR with the PRISMA protocol, searching articles in Google Scholar and Garuda databases using the keywords “gamification,” “mathematical concept understanding,” and “self-efficacy” published between 2016 and 2026, with Sinta 1–4 or Scopus accreditation. A total of 25 articles were identified 20 from Google Scholar and 5 from Garuda and after applying inclusion and exclusion criteria, 14 articles were selected for content analysis. The results show that gamification significantly improves students’ mathematical concept understanding by making abstract material more concrete and increasing student engagement. Gamification also positively affects students’ self-efficacy through immediate feedback and reward systems. Moreover, there is a strong positive relationship between self-efficacy and mathematical concept understanding, where students with high self-efficacy tend to master more indicators of concept understanding. Therefore, integrating gamification into mathematics learning is an effective strategy to enhance both cognitive and affective aspects of student achievement.